2023
DOI: 10.3389/fmicb.2023.1117355
|View full text |Cite
|
Sign up to set email alerts
|

Bio-organic fertilizers improve Dendrocalamus farinosus growth by remolding the soil microbiome and metabolome

Abstract: Organic and microbial fertilizers have potential advantages over inorganic fertilizers in improving soil fertility and crop yield without harmful side-effects. However, the effects of these bio-organic fertilizers on the soil microbiome and metabolome remain largely unknown, especially in the context of bamboo cultivation. In this study, we cultivated Dendrocalamus farinosus (D. farinosus) plants under five different fertilization conditions: organic fertilizer (OF), Bacillus amyloliquefaciens bio-fertilizer (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 99 publications
(103 reference statements)
2
4
0
Order By: Relevance
“…This parallels with earlier reports of shifts in SOM composition due to long-term FYM addition, including higher molecular weight and carboxyl contents (Ellerbrock et al, 1999). Multiple studies reported increased abundances of non-polar, aliphatic, oxidized an N-containing compounds (most likely fatty acids, and amino acids) (Gerzabek et al, 2006;Ye et al, 2019;Shi et al, 2022;Li et al, 2023;Tang et al, 2023) and decreased abundances of phenolics or aromatic signals upon continued manure addition (Mao et al, 2008;Shi et al, 2022;Tang et al, 2023). We did not find elevated N in markers related to Cat.…”
Section: Transformation Processes Drive Changes In Som's Energetic Po...supporting
confidence: 91%
See 2 more Smart Citations
“…This parallels with earlier reports of shifts in SOM composition due to long-term FYM addition, including higher molecular weight and carboxyl contents (Ellerbrock et al, 1999). Multiple studies reported increased abundances of non-polar, aliphatic, oxidized an N-containing compounds (most likely fatty acids, and amino acids) (Gerzabek et al, 2006;Ye et al, 2019;Shi et al, 2022;Li et al, 2023;Tang et al, 2023) and decreased abundances of phenolics or aromatic signals upon continued manure addition (Mao et al, 2008;Shi et al, 2022;Tang et al, 2023). We did not find elevated N in markers related to Cat.…”
Section: Transformation Processes Drive Changes In Som's Energetic Po...supporting
confidence: 91%
“…Accumulation of SOC upon OM inputs, including FYM, have been accurately modelled using one parameter (h for "humification", linked to the fraction of remaining C) but the molecular mechanisms behind that parameter are poorly understood (Levavasseur et al, 2020). Molecular-level analyses using a wide range of methods have reported increases in aliphaticity, carboxyl-C, peptides, lipids and lipidlike molecules, oxygen-enriched compounds, nonpolar alkyl compounds (likely fatty acids), alkyl C, alkyl-O C and di-O-alkyl C over a simultaneous decrease in phenolics and aromatic C as compared to control treatments (Ellerbrock et al, 1999;Gerzabek et al, 2006;Mao et al, 2008;Ye et al, 2019;Shi et al, 2022;Li et al, 2023;Tang et al, 2023). In contrast, some studies have reported an increase of aromatic structures or lignin, and recalcitrance upon receiving organic amendments (Leifeld et al, 2002;Peltre et al, 2017;Ye et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, there is a large portion of the Archaea phylum Crenarchaeota in the CFSF2 group. The phylum Crenarchaeota is most commonly abundant in marine environments [52]. However, there are some novel Crenarchaeota found in forest and also paddy soil [53,54].…”
Section: Microbial Diversity In Sf-supplemented Soilsmentioning
confidence: 99%
“…The use of biofertilizer, which contains helpful microorganisms, helps to slow down the breakdown of organic matter and improve the availability of vital plant nutrients, including nitrogen, phosphorous, sulfur and phosphorous (Jena et al, 2020). As a result, the presence of beneficial microbes in biofertilizers increases soil water retention, stimulates soil aggregate growth (Li et al, 2023), and has a buffering impact on soil acidity, alkalinity, salinity, harmful heavy metals, and, pesticides (Yengkokpam et al, 2022). Furthermore, biofertilizer could reduce the cost of production, and eco-friendly, and renewable sources of plant nutrients (Sarker et al, 2018).…”
Section: Introductionmentioning
confidence: 99%